2017
DOI: 10.1016/j.jvs.2016.10.100
|View full text |Cite
|
Sign up to set email alerts
|

Angiosome-directed revascularization in patients with critical limb ischemia

Abstract: DR significantly improves wound healing and major amputation rates after endovascular treatment in patients with CLI, supporting the angiosome theory. In the presence of collaterals, outcomes after IR are similar to outcomes after DR. Alternatively, patients without collaterals may benefit even more from DR as a primary treatment strategy. The angiosome theory is less applicable in bypass surgery, because bypasses are generally anastomosed to the least affected artery, with runoff passing the ankle to maintain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 41 publications
4
61
1
1
Order By: Relevance
“…Historically, the aim of revascularization in patients with PAD has been to achieve inline pulsatile flow to the foot, usually by targeting the best vessel available. However, more recently, the angiosome‐directed approach has been advocated but remains a subject of much debate . According to this theory, the foot can be divided into three‐dimensional blocks of tissue, each with its own feeding artery.…”
Section: Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Historically, the aim of revascularization in patients with PAD has been to achieve inline pulsatile flow to the foot, usually by targeting the best vessel available. However, more recently, the angiosome‐directed approach has been advocated but remains a subject of much debate . According to this theory, the foot can be divided into three‐dimensional blocks of tissue, each with its own feeding artery.…”
Section: Treatmentmentioning
confidence: 99%
“…However, because of lack of clear definitions and factors like selection bias, the effectiveness of the angiosome concept in patients with diabetes is unknown . Particularly in patients with diabetes who usually have poor collaterals, restoration of flow to an artery directly supplying the affected area seems the best approach during an endovascular procedure . Successfully opening one or more occluded vessels is not the same as a clinically successful procedure and before the procedure is terminated blood flow to the ulcer area should therefore be assessed.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Those of one study suggest that indirect endovascular revascularisation through collaterals has similar outcomes to direct revascularisation and that both offer significantly improved rates of limb salvage and wound healing when compared to indirect revascularisation without collaterals. These findings are reflected in two recent meta‐analyses that combined include >4000 limbs with foot ulcers (>80% of which had diabetes), which both concluded that endovascular IR significantly improves wound healing and major amputation rates, but that, in the presence of collaterals, IR and DR have similar outcomes . However, the populations included were highly variable, the definitions poorly defined and it is not possible to draw any firm conclusions from these data.…”
Section: Discussionmentioning
confidence: 99%